Natural characteristics of Hor Al-Musandak (Journal of the College of Basic Education, 2024)
the study area is part of the sedimentary plain that was formed as a result of the receding of the watersof the Arabian Gulf as aresult of the accumulation of silt coming with Euphrates rivers and the valleys that descend form the Iraq _iran borders ,som of these formations are covered lnconsistently with quaternary sediments,asfor the climate ,of the study area, it ischaracterized by being cold and rainy in winter and along and dry summer with tow transitional season spring and autumn.